The Transformation of Islamic Education in The Era of Artificial Intelligence (AI): Opportunities, Challenges, and Ethics of Its Use - Rosmaini, Rosmaini (Teunuleh Publisher, 2025)
The transformation of Islamic education in the era of artificial intelligence (AI) opens up great opportunities to improve the quality, effectiveness, and relevance of learning. This article aims to examine in depth the potential, challenges, and ethical framework in the use of AI for Islamic education. Using the literature review method, various scientific literature is thematically analyzed to identify patterns, findings, and strategic recommendations. The results of the study show that AI is able to provide a more personalized, adaptive, and efficient learning experience through features such as chatbots, automated evaluations, and interactive learning. However, significant challenges also arise, including limited infrastructure, low digital competence of teachers, unprepared curriculum, and concerns about the degradation of human and spiritual values. The key findings of this article are that AI integration should be governed within an Islamic ethical framework centered on the principles of sharia maqashid, specifically hifz al-din (protection of religion) and hifz al-aql (protection of reason). This article contributes by offering a character-centric model of AI integration and positioning AI as a tool that is subject to humanist values, rather than as an essential substitute for the role of murabbi. A comprehensive strategy is needed, including curriculum reform, strengthening teacher competence, and ethical regulations based on local wisdom. This article offers a comprehensive technology integration strategy through curriculum updates, strengthening teachers' digital competencies, cross-sector collaboration, and the development of contextual Islamic learning content.